The online environmental library of the Province of Cremona - Cameron, Enrico (BORNH Bulletin of Regional Natural History, 2022)
This short communication briefly describes the online library provided by the Environment and Territory Department of the Province of Cremona administration and the library database that was produced as part of this work. The publications in the library are freely available and primarily concern the ecology and environment of the River Po basin. The database includes a fully searchable list of the publications titles and topic labels meant to help its consultation by the general public; moreover, it is open access and can be downloaded through the Zenodo multi-disciplinary open repository.